A Novel Pixel-Based Reconfigurable Antenna Applied in Fluid Antenna Systems With High Switching Speed - Jichen Zhang; Junhui Rao; Zan Li; Zhaoyang Ming; Chi-Yuk Chiu; Kai-Kit Wong; Kin-Fai Tong; Ross Murch (IEEE Open Journal of Antennas and Propagation)
Fluid Antenna Systems (FASs) have recently been proposed for enhancing the performance of wireless communication. FAS have previously exploited mechanical movement or liquids to perform the required adaptation to the wireless environment. Due to the mechanical or liquids approach, these systems have limited switching speeds that prevents their use for packet-by-packet adaptation in wireless communication systems. In this paper, we demonstrate that using mechanical movement or liquids in FAS is equivalent to radiation pattern reconfiguration. Using this observation, we propose a pixel-based reconfigurable antenna design for FAS (PRA-FAS) that supports microsecond FAS port switching for packet-by-packet adaptability. The proposed PRA-FAS provides 12 FAS ports across an equivalent length of 1/2 wavelength. Simulation and experimental results of a PRA-FAS prototype operating at 2.5 GHz indicate that the PRA-FAS can meet the FAS requirements, including port correlation and impedance matching. System-level simulations and experiments, using a MIMO testbed, demonstrate that the correlation of PRA-FAS ports aligns well with those that use mechanical movement or liquids.